Betaglucan as an immunomodulatory agent for children: An integrative review (Research, Society and Development, 2023)
Betaglucan is a polymer present on the cell wall of several compounds. Its structure is capable of interacting with the body's defense cells, stimulating them. For many years the immunomodulatory properties of this polymer have been studied. Objective: This study aimed to establish a positive association between the use of beta-glucan and the increase of immunity in children. Methodology: The integrative review was carried out in the main databases online. Final considerations: several studies have pointed to beta-glucan as a possible immunomodulator, which is a reality, easily, accessible and inexpensive.